Vimentin expression and the influence of Matrigel in cell lines of head and neck squamous cell carcinoma - Aluana Maria da Costa Dal Vechio; Fernanda Salgueiredo Giudice; Felipe Fornias Sperandio; Andrea Mantesso; Décio dos Santos Pinto Junior (Sociedade Brasileira de Pesquisa Odontológica, 2011)
Vimentin is a cytoeskeletal intermediate filament protein commonly observed in mesenchymal cells; however, it can also be found in malignant epithelial cells. It is demonstrated in several carcinomas, such as those of the cervix, breast and bladder, in which it is widely used as a marker of the epithelial to mesenchymal transition that takes place during embryogenesis and metastasis. Vimentin is associated with tumors that show a high degree of invasiveness, being detected in invasion front cells. Its expression seems to be influenced by the tumor microenvironment. The aim of this study was to evaluate vimentin expression in head and neck squamous cell carcinoma (HNSCC) cell lines, and to investigate the contribution of the microenvironment to its expression. HNSCC cell lines (HN6, HN30 and HN31) and an immortalized nontumorigenic cell line (HaCaT) were submitted to a three-dimensional assay with Matrigel. Cytoplasmatic staining of the HN6 cell line cultured without Matrigel and of the HN30 and HN31 cell lines cultured with Matrigel was demonstrated through immunohistochemistry. Western Blotting revealed a significant decrease in vimentin expression for the HN6 cell line and a significant increase for the HN30 and HN31 cell lines cultured with Matrigel. The results suggest that vimentin can be expressed in HNSCC cells and its presence is influenced by the microenvironment of a tumor.